Glebych minutissimus gen. et sp. nov., the smallest cobweb spider (Araneae: Theridiidae) - Eskov, Kirill Y.; Marusik, Yuri M. (Zootaxa, 2021)
Glebych minutissimus gen. et sp. n., (♂♀), a minute six-eyed and apparently lungless theridiid spider, inhabiting epiphytes in foggy-forest belt at Peruvian Andes is described, representing the smallest (total length varies from 0.79 to 0.92 mm, carapace length ca. 0.36 mm) member of the family. Glebych gen. n. is related to the Neotropic genus Styposis Simon, 1894, which is small-sized and six-eyed as well.